2020
DOI: 10.3390/ijerph17207507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yangsaeng (Health Management) Therapy for Korean Older Adults in Nursing Home

Abstract: The number of older adults admitted to nursing homes is steadily increasing, and the health management for them is a very important issue in Korean society. This study aimed to examine the effects of Yangsaeng (health management) therapy on physical health status, depression, life satisfaction, and Yangsaeng (health management) of Korean older adults in nursing homes. A quasi-experimental study design using a pretest-posttest control group was employed. Study participants were a total of 80 older adults (inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…In the intervention group, health status was significantly improved after participating in the cognitive/exercise dual-task program. This was consistent with the results of previous studies showing that various exercise programs were effective on the health status of the elderly [14,15,32]. In this study's cognitive/exercise dual-task program, it was confirmed that performing fumanet exercise with friends and sharing opinions using photo cards resulted in the health status improvement of the elderly living in the community.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the intervention group, health status was significantly improved after participating in the cognitive/exercise dual-task program. This was consistent with the results of previous studies showing that various exercise programs were effective on the health status of the elderly [14,15,32]. In this study's cognitive/exercise dual-task program, it was confirmed that performing fumanet exercise with friends and sharing opinions using photo cards resulted in the health status improvement of the elderly living in the community.…”
Section: Discussionsupporting
confidence: 92%
“…This supports the results of this study by showing that exercise programs have a positive effect on the life satisfaction of the elderly. In addition, a previous study showed that life satisfaction was increased by performing exercise therapy for the elderly with low back pain [14]. Life satisfaction is a subjective feeling, and as the pain or stress chronically experienced by the elderly living in the community is reduced, satisfaction can increase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations